Chemically Sustainable and Green One‐Pot Multicomponent Synthesis of Highly Functionalized Polycyclic N‐Fused‐Pyrrolidine Heterocycles. Issue 2 (15th January 2018) - Yan, Li‐Jun; Wang, Jun‐Liang; Xu, Dan; Burgess, Kevin S.; Zhu, Ai‐Fei; Rao, Yan‐Ying; Chen, Xue‐Bing; Wang, Yong‐Chao
Abstract: An eco‐friendly, highly‐eﬃcient, atom‐economical three‐component cascade reaction of acenaphthenequinone (8 ), β ‐nitroolefins (9 ) and α ‐amino acid (10 ) in MeOH/H2 O is developed for the synthesis of novel functionalized polycyclic N ‐fused‐pyrrolidine derivatives (11 ). All products are obtained by filtration in the absence of column chromatography and recrystallization. Due to its operational simplicity, this green and chemically sustainable reaction can be easily applied toward the design and synthesis of target molecules for the discovery of novel biologically active compounds. Abstract : A series of novel functionalized polycyclic N ‐fused‐pyrrolidine derivatives are synthesized by a three‐component cascade reaction in aqueous medium. All products are obtained by simple filtration in the absence of column chromatography and recrystallization operation. This green and chemically sustainable reaction can be easily applied toward the design and synthesis of target molecules for the discovery of novel biologically active compounds.